PENGARUH DIGITAL MARKETING TERHADAP MINAT BELI DAN KEPUTUSAN PEMBELIAN PROPERTI KOTA BATAM - Eryc; Chris (P3M Institut Teknologi Pagar Alam, 2023)
Digital marketing has certified to be an efficacious way to get customers to buy and increase sales. This study focus to present a case that has proven the efficacious in digital marketing strategies. The sampling method is non-random (non-probability sampling) using purposive sampling techniques with a sample size of 30-500 respondents. This research used approach on this study is a quantitative research. Validity tests, Reliability tests, Classical assumption tests, Regression analyses, coefficient of determination tests and hypothesis were used for data analysis. The results to be achieved are the outcome of empirical significance testing, the influence of the digital marketing variable (X1) on the buying variable (Y1), the influence of buying interest (x2) on the purchasing decision variable (Y2), and the influence of the digital marketing variable (X1) on the decision variable. Simultaneous purchases (Y2) can be accepted with a significant effect on use results as suggestions for Batam property sector players who promote digital marketing methods. The outcome of the study shows that selecting the right digital marketing and good content management can escalate sales.